Working conditions in hospitals revisited: a moderated-mediated model of job context and presenteeism - Mach, M.; Ferreira, A. I.; Martinez, L. F.; Lisowskaia, A.; Dagher, G. K.; Perez-Nebra, A. R. (PLoS One, 2018)
This study examines whether the relationship between the employees' perceived job autonomy may be prone to the contextual influence of supervisor support and presenteeism climate in explaining the attendance behaviors of presenteeism-the employees' decision to attend work despite being ill or not feeling well. Does work context play a role on presenteeism climate and the specific act of presenteeism? This study includes 213 health care employees (e.g., nurses, doctors) working in one private hospital in Lebanon. We used the ordinary least squared (OLS) regressions path analytical framework and bootstrapping methods to estimate the hypothesized moderated-mediation models. Our findings indicate that healthcare job resources (job autonomy) is correlated with the presenteeism climate and the occurrence of presenteeism attendance behaviors. We also found that this relationship is mediated by presenteeism climate and that supervisor support moderates the observed indirect relationship. This study extends the organizational attendance research domain to presenteeism climate by explaining for both doctors and nurses how contextual variables explains the relationship between jobs resources and presenteeism attendance behaviors. Supervisor support plays an important role in encouraging task autonomy and thus allowing employees increase their perception of empowerment to manage their actions at work. Overall, healthcare managers should ensure that employees understand their roles and duties and have an up-to-date, clearly defined role (e.g., job description) so that they can meet their organizations' goals.